2016
DOI: 10.1186/s12913-016-1602-4
|View full text |Cite
|
Sign up to set email alerts
|

Perception of quality of health delivery and health insurance subscription in Ghana

Abstract: BackgroundNational health insurance schemes (NHIS) in developing countries and perhaps in developed countries as well is a considered a pro-poor intervention by helping to bridge the financial burden of access to quality health care. Perceptions of quality of health service could have immense impacts on enrolment. This paper shows how perception of service quality under Ghana’s insurance programme contributes to health insurance subscription.MethodsThe study used the 2014 Ghana Demographic and Health Survey (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 30 publications
3
34
2
Order By: Relevance
“…Two (15.4%) studies each reported evidence from Burkina Faso and Tanzania, and one (7.7%) each reported from Niger, Sierra Leone, and Nigeria. Eight out of the 13 included studies were conducted in health facility-based settings [4,5,17,[50][51][52][53][54], two in a household-based based setting [11,55], two in community-based settings [56,57], and one was a national survey [58]. The majority (38%) of the included articles were cross-sectional studies [5,17,51,54,56], whilst the minority (8%) was quasi-experimental study design [52] (Fig.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Two (15.4%) studies each reported evidence from Burkina Faso and Tanzania, and one (7.7%) each reported from Niger, Sierra Leone, and Nigeria. Eight out of the 13 included studies were conducted in health facility-based settings [4,5,17,[50][51][52][53][54], two in a household-based based setting [11,55], two in community-based settings [56,57], and one was a national survey [58]. The majority (38%) of the included articles were cross-sectional studies [5,17,51,54,56], whilst the minority (8%) was quasi-experimental study design [52] (Fig.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…2). Twelve of the included articles reported evidence on clients' perspective of the quality of maternal healthcare based on free maternal healthcare financing policies [4,5,11,17,[50][51][52][53][54][55][56]58] and one study based on partially free maternal healthcare financing policy [57].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations